Avaliação dos atributos físicos de um argissolo cultivado com cana-de-açúcar em área com adequação de relevo, utilizando equipamento de preparo profundo e canteirizado do solo - Marasca, Indiamara [UNESP] (2014)
Unlike traditional techniques of soil management, the quest for soil preparation to be able to maintain the productivity of fields and, consequently, its competitiveness in the market, not affecting the environment, has driven new technologies to rural areas. With Deep Bed tillage, the plants root system increases due to a better aeration and lower soil penetration resistance, making easier the water and nutrients absorption, providing further development and productivity. This study aimed to evaluate the behavior of soil physical properties in two sugar cane planting areas, one of them being managed with Deep Bed tillage equipment and the other one being managed with conventional tillage methods. The experiment was conducted in Lençóis Paulista, São Paulo at PHD Company belonging to Zilor group. The analyzed variables were soil penetration resistance and relative density. For managements it was valued the amount of organic matter, and for the culture, it was valued tillering, stalk diameter, height of sugar cane and its Productivity. The soil cone Index (SCI) presented lower values in the Deep Bed Tillage without traffic (PPC without traffic) for all layers in comparison to Deep Tillage with traffic (PPC with traffic) and Conventional Tillage (PC). For both soil tillage treatments, the Soil Relative Density (DRS) was fit to layer 0 to 0.15 m, but in layers 0.15 to 0.30m and 0.30 to 0.45 m it was considered detrimental to the culture development. The soil erosion index was considered of high risk for Paleudult - Yellow soil. The values of soil organic matter in the first year of sugar cane harvesting showed no significant difference between treatments. The tillering was higher for Deep Bed Tillage (PPC) when compared to conventional tillage (PC) at the 120th day after sugar cane planting and after the first harvesting, and the plant height only showed higher values for the PPC at 390th day after ...